2017
DOI: 10.1073/pnas.1708727114
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic conformational changes of a coronavirus spike glycoprotein promote membrane fusion

Abstract: The tremendous pandemic potential of coronaviruses was demonstrated twice in the past few decades by two global outbreaks of deadly pneumonia. The coronavirus spike (S) glycoprotein initiates infection by promoting fusion of the viral and cellular membranes through conformational changes that remain largely uncharacterized. Here we report the cryoEM structure of a coronavirus S glycoprotein in the postfusion state, showing large-scale secondary, tertiary, and quaternary rearrangements compared with the prefusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
694
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 561 publications
(714 citation statements)
references
References 65 publications
16
694
0
4
Order By: Relevance
“…We showed that in vitro trypsin cleavage of MHV, SARS-CoV and MERS-CoV S, under limited proteolysis conditions, recapitulated fusion activation by inducing the pre-to postfusion transition (Walls et al, 2017b). The cryoEM structure of the MHV S 2 subunit ectodomain trimer revealed that membrane fusion involves large-scale S conformational changes that are reminiscent of the ones described for other class 1 fusion proteins, including the pneumovirus/paramyxovirus F glycoproteins ( Fig.…”
Section: Mechanism Of Fusion Activationmentioning
confidence: 63%
See 2 more Smart Citations
“…We showed that in vitro trypsin cleavage of MHV, SARS-CoV and MERS-CoV S, under limited proteolysis conditions, recapitulated fusion activation by inducing the pre-to postfusion transition (Walls et al, 2017b). The cryoEM structure of the MHV S 2 subunit ectodomain trimer revealed that membrane fusion involves large-scale S conformational changes that are reminiscent of the ones described for other class 1 fusion proteins, including the pneumovirus/paramyxovirus F glycoproteins ( Fig.…”
Section: Mechanism Of Fusion Activationmentioning
confidence: 63%
“…Upon receptor binding and proteolytic cleavage at the S 1 /S 2 and S 2 0 sites, the S 1 crown is likely shed (as observed for MERS-CoV S by Yuan et al, 2017) to facilitate a conformational change of S 2 , which involves projection of the fusion peptide to a distance of 100 Å and its insertion into the target membrane ( Fig. 3) (Walls et al, 2016a(Walls et al, , 2017b. The free energy released upon S 2 refolding from the prefusion to the postfusion state is believed to bring the viral and host membranes in close proximity and promote membrane merger (Harrison, 2008).…”
Section: Mechanism Of Fusion Activationmentioning
confidence: 98%
See 1 more Smart Citation
“…Coronavirus entry into host cells is mediated by the trimeric transmembrane spike (S) glycoprotein. S is composed of two functional subunits responsible for binding to the host cell receptor (S 1 subunit) and fusion of the viral and cellular membranes (S 2 subunit) (Gui et al, 2017;Kirchdoerfer et al, 2016;Pallesen et al, 2017;Shang et al, 2017Shang et al, , 2018Walls et al, 2016aWalls et al, , 2016bWalls et al, , 2017Xiong et al, 2017;Yuan et al, 2017). We have previously determined structures of the mouse hepatitis virus (MHV) S ectodomain in the pre-fusion and post-fusion states, which provided snapshots of the start and end points of the membrane fusion reaction (Walls et al, 2016a.…”
Section: Introductionmentioning
confidence: 99%
“…The N and C-terminal ends of the gp41 subunit in black are marked. The two lower panels show a representative structure of the coronavirus postfusion CSU trimers displayed as ribbons (middle) and as surface representation (bottom) (Walls et al, 2017) with the N-and C-terminal ends visible in the structure of the ectodomain indicated in blue and red, respectively. A schematic on the ribbon diagram shows the expected location of the missing segments in the intact postfusion protein on membranes (not present in the structure; blue at the N-terminal end, connecting to the fusion peptide inserted superficially on the outer lipid leaflet of the fused membranes, represented as a full blue rectangle) and the C-terminal end in red, connecting to the TM helices and the cytosolic tail.…”
Section: Class I Fusion Proteinsmentioning
confidence: 99%